The Transformation of Kizukai Habitus on Asian Trainee in Japan: Striving and Competition of Labor Market in ASEAN - Prabowo, Roberto Masami; Mahzuni, Dade; Risagarniwa, Yuyu Yohana; Rustam, Muhammad Reza (JAS (Journal of ASEAN Studies), 2024)
In the 1990s, Japan faced a severe economic downturn known as the "Lost Decade." To address labor shortages and strengthen economic and political ties with developing nations, the Japanese government has initiated a trainee program to provide individuals from developing countries in Asia with the opportunity to gain work experience in Japan for three years. The research aims to explore the impact of Japan's trainee program on participants who left Japan between 2000 and 2010. Specifically, it investigates how these individuals adapt to Japanese society through the concept of ‘kizukai’ (empathy and concern for others) and examines their success in establishing businesses in their home countries. The research employs an ethnographic approach, utilizing direct interviews and a literature review. The ethnographic method, utilizing direct interviews with former trainees, offers qualitative insights into their social adaptation, business success, and engagement with Japanese cultural practices, enriching the understanding of their lived experiences. The literature review complements this by providing a theoretical framework, particularly Bourdieu's theories of habitus, field, and capital, to analyze the changes in trainees' behaviors and their impact on business practices. The research finds that many trainees have successfully integrated into Japanese society by internalizing Hiroyuki Inoue's concept of kizukai. This integration plays a significant role in their entrepreneurial success upon returning to their home countries, where they establish prosperous businesses. The findings suggest that while the trainee program has shortcomings, it contributes to strengthening international economic relations and offers lessons for improving future trainee programs.